2018
DOI: 10.1093/gbe/evy180
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Basis of Feather Diversity in Birds

Abstract: Feather diversity is striking in many aspects. Although the development of feather has been studied for decades, genetic and genomic studies of feather diversity have begun only recently. Many questions remain to be answered by multidisciplinary approaches. In this review, we discuss three levels of feather diversity: Feather morphotypes, intraspecific variations, and interspecific variations. We summarize recent studies of feather evolution in terms of genetics, genomics, and developmental biology and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 144 publications
1
33
1
Order By: Relevance
“…These differences not only attain species but also certain domestic breeds or even varieties [57]. Given the varieties may present different sexual dimorphism patterns, there is a relatively strong possibility that sex determination methods may not be valid across the same varieties of a particular breed.…”
Section: Discussionmentioning
confidence: 99%
“…These differences not only attain species but also certain domestic breeds or even varieties [57]. Given the varieties may present different sexual dimorphism patterns, there is a relatively strong possibility that sex determination methods may not be valid across the same varieties of a particular breed.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in Table 1 , α-keratin mainly occurs in mammals, while β-keratin is the major component of avian and reptilian tissues. In fact, β-keratin is found only in avian and reptilian epidermis (though one mammal, the pangolin, a unique scaly anteater, has been reported to have both α- and β-keratin in the keratin scales that cover its skin ( Wang et al, 2016 )), whereas α-keratin is found in mammalian as well as in avian and reptilian keratin ( Alibardi, 2003 ; Greenwold et al, 2014 ; Ng and Li, 2018 ). The α-keratin found in the epidermis located between the scales in reptiles and in feathers is responsible for the mechanical strength of the epithelial cells, their adhesiveness, and the changes in shape when stretched ( Alibardi, 2007 ; Skieresz-Szewczyk et al, 2017 ).…”
Section: Essentials Of Keratin Biomass As Substrate For Keratinolyticmentioning
confidence: 99%
“…By contrast, the β-keratin in reptile scales exhibits limited extensibility yet significant microbiological resistance and hydrophobicity, and serves a protective function in nature ( Calvaresi et al, 2016 ). In addition, some believe that α- and β-keratins are completely unrelated evolutionarily, and it has even been proposed recently that β-keratins should be renamed as corneous β-proteins ( Ng and Li, 2018 ).
Fig.
…”
Section: Essentials Of Keratin Biomass As Substrate For Keratinolyticmentioning
confidence: 99%
“…Previous studies reported the formation, morphogenesis, differentiation, and maturation of the skin and feather follicles (Yu et al 2002;Lin et al 2006;Chen et al 2017). Recently, transcriptomic analysis have been conducted to identify candidate genes (gene expression patterns) involved in differentiation, growth regulation, survival, and morphogenesis of different types of feathers (in adults) and embryonic integuments of ducks, chicken and goose (Anser anser) (Ng and Li 2018;Liu et al 2018;Lowe et al 2015). Furthermore, Sello et al (2019) only reported a single time point during the embryonic skin development performance evaluation transcriptome between Anser anser and Anser cygnoides.…”
mentioning
confidence: 99%